ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN MERGER DAN AKUISISI PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Kumaradewi, Ni Putu Dhanan; Candradewi, Made Reina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p15, 2023)
Merger and acquisition activities are corporate action activities that often occur in Indonesia, especially in the banking sector. Merger and acquisition activities abnormal return of shares and trading volume activities (TVA) . In this case the merger activity and gives a signal to investors to invest. This study aims to examine the capital market against banking industry companies that carry out mergers and acquisitions on the Indonesia Stock Exchange as seen through abnormal stock returns and TVA. There are 14 companies conducting mergers and acquisitions from 2001 to 2021 on the Indonesia Stock Exchange (IDX). The method that used by this event study with non-probability sampling method, namely purposive sampling technique. The data analysis technique used was the Wilcoxon signed rank test. The results showed that there were no significant market differences before and before the announcement of mergers and acquisitions. Another thing found is the announcement of mergers and acquisitions significant differences in TVA before and before mergers and acquisitions.